Quality index for evaluation of public green areas - Souza, Mariana Cristina da Cunha; Amorim, Margarete Cristiane Costa Trindade [UNESP] (Universidade Federal de Goias, 2019)
In geographic science it is common to propose procedures for the analysis of environmental quality, structured from existing environmental indicators in the landscape, which are capable of qualitative and quantitative measurement. Thus, the objective of this article is to reflect on the systematization of the Green Area Quality Index (IQA) applied in the urban area of Presidente Prudente (SP) and to highlight the importance of the choice of indicators in the index elaboration process. The proposal reflects a methodological effort in the development of environmental assessment techniques, proving feasible both for the systematization and standardization of primary and secondary data and for the identification of quality standards in the urban scale and in a spatial and temporal perspective.
Índice de calidad para la evaluación de áreas verdes públicas
Índice de qualidade para avaliação de áreas verdes públicas
Keywords: Environmental indicators; Environmental Quality; Public spaces; Urban space